Infections in the natural environment of British Columbia, Canada - Nevio Cimolai; Tomas Cimolai (Elsevier, 2008)
Summary: The Canadian province of British Columbia has a luxurious environment, complete with the multitude of wildlife and insects, and would at first glance appear to be suitable for the transmission of diseases in nature communicable to humans. Despite this potential, such diseases are relatively uncommon, although several have the potential for serious consequences. Attention has been recently focused on hantavirus infection, water-borne toxoplasmosis and parasitic diarrheal diseases, cryptococcosis on Vancouver Island, and rabies. West Nile virus has not yet caused endemic human infection in this province as of 2008. We review the cumulative science in this area. Keywords: Infection, Zoonosis, British Columbia, Western Canada